Towards new emancipatory horizons: autonomous politics in urban groups of Mexico and Chile - Valenzuela Fuentes, Katia (2017)
Recent decades have witnessed the emergence of powerful social movements and community initiatives across Latin America. These collective projects have developed a strong anti-systemic critique, refusing state-centred and top-down approaches to social change and seeking to prefigure in the present the social world in which they want to live in. At a micro scale, the political organizing around grassroots groups or colectivos has become a popular strategy for Latin American activists living in the city. Inspired by this phenomenon, this thesis analyses the politics of autonomy enacted by colectivos in Latin America. More specifically, it examines how the politics of autonomy is understood by Chilean and Mexican colectivos; the dimensions, organizational structures and strategies shaping their praxis; the main challenges encountered in the ‘doing’ of autonomous politics; and its potential for the prefiguration of a radical approach to social change.